Bio-oils and diesel like fuel derived from alkaline treated empty fruit bunch (EFB) - Saidina Amin, Nor Aishah (International Journal of Biomass & Renewables, Universiti Teknologi Petronas, 2012)

(untitled)
In this work, EFB was chemically pretreated with different sodium hydroxide (NaOH) concentration. Pyrolysis was conducted in the presence of HZSM-5 after the pretreatment step to assess the efects of pretreatment process on bio-oil production. Conversions of EFB were reported to be 61 wt%, 47 wt% and 42 wt%, after pretreatment with 5 wt%, 15 wt% and 25 wt%, NaOH concentrations, respectively. Furthermore, the pretreatment has efectively improved the bio-oil quality by reducing or even eliminating undesired products. Besides, biomass structure was dissembled and converted to valuable compounds after upgrading the bio-oil with improved quality.